Autosomal-dominant Leber Congenital Amaurosis Caused by a Heterozygous CRX Mutation in a Father and Son. (June 2015) - Arcot Sadagopan, Karthikeyan; Battista, Robert; Keep, Rosanne B.; Capasso, Jenina E.; Levin, Alex V.
Abstract Background: Leber congenital amaurosis (LCA) is most often an autosomal recessive disorder. We report a father and son with autosomal dominant LCA due to a mutation in the CRX gene. Materials and Methods: DNA screening using an allele specific assay of 90 of the most common LCA-causing variations in the coding sequences of AIPL1, CEP290, CRB1, CRX, GUCY2D, RDH12 and RPE65 was performed on the father. Automated DNA sequencing of his son examining exon 3 of the CRX gene was subsequently performed. Results: Both father and son have a heterozygous single base pair deletion of an adenine at codon 153 in the coding sequence of the CRX gene resulting in a frameshift mutation. Conclusion: Mutations involving the CRX gene may demonstrate an autosomal dominant inheritance pattern for LCA.